Special needs in the early years partnership and participation - Crutchley, Rebecca (SAGE, 2018)
Fully up to date with the SEND Code of Practice, this book explores all the key contemporary issues relevant to supporting children with special needs in an early years context. Combining theory with practice, it demonstrates how to ensure children's individual needs are at the heart of early years provision.